If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12(k + -4) = 60 Reorder the terms: -12(-4 + k) = 60 (-4 * -12 + k * -12) = 60 (48 + -12k) = 60 Solving 48 + -12k = 60 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-48' to each side of the equation. 48 + -48 + -12k = 60 + -48 Combine like terms: 48 + -48 = 0 0 + -12k = 60 + -48 -12k = 60 + -48 Combine like terms: 60 + -48 = 12 -12k = 12 Divide each side by '-12'. k = -1 Simplifying k = -1
| 18x^3-50x=0 | | x+(2x+0.60)+(x+0.20)=7.2 | | x^3+15x^2+80x-125.57=0 | | 3+7x=63 | | 3x^2-20x=100 | | 7-2x+2(3-6)=3-3.4 | | 125.57-80x-15x^2-x^3=0 | | 102+3x=10x+24 | | 4x+15=-96-7x | | 20=4x-2 | | 3x=6-3-12-18 | | -6m+12+7m=-2 | | 0.06*5000= | | 0.06*5= | | f-32=1.8*23 | | 6(x-5)+5(x-1)=10x-7 | | 10x+5=8x+29 | | 5+8x=-3 | | (x+10)(x-7)= | | 7(1+2v)-2v=2(v+3) | | 43+43= | | 19x+6x^2+18=3 | | 3x^2-5x-2.25=0 | | -8(6n+4)=-320 | | -2x=10-18 | | (2x-5+x)2=38 | | 6(-6+5b)=-156 | | 12x=3x-45 | | x/6-7=-6 | | 7x=32-4 | | x(3x-2)-18x=5x(2-3x)+6 | | (x+6+9)2=52 |